PENGETAHUAN WANITA USIA SUBUR TENTANG COVID-19 BERHUBUNGAN DENGAN PARTISIPASI VAKSINASI COVID-19 - Ade Putri Avilia; Yopi Wulandhari; Anjeli Ratih Syamlingga Putri; Restianingsih Putri Rahayu (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2022)
Covid-19 is a new virus that was discovered to have attacked humans in 2019. On February 16, 2020, the World Health Organization (WHO) reported 51,857 confirmed cases in 25 countries with 1,699 deaths. To stop the transmission of Covid-19, Indonesia is promoting a vaccination program for the Indonesian population, including reproductive women. The purpose of this study is to find out how the relationship between knowledge about Covid-19 of reproductive women and participation in carrying out Covid-19 vaccinations in the Pangkalan Kasai Health Center Working Area in 2022. This research method uses an analytical method with a cross sectional approach and sampling with the Snowball sampling method. Data analysis used univariate and bivariate analysis which was tested using the Chi-square test using the SPSS application. This research was obtained in the Pangkalan Kasai Public Health Center in 2022, totaling 100 respondents by distributing questionnaires. The majority of reproductive women knowledge levels about Covid-19 were in the good category as many as 59 respondents (59%). Reproductive women participated in the Covid-19 vaccination as many as 93 respondents (93%). The results of statistical analysis showed p-value = 0.00 (α < 0.05) which stated that there was a relationship between reproductive women knowledge about Covid-19 and participation in carrying out Covid-19. Conclusions in this study knowledge about Covid-19 can increase reproductive women participation in carrying out Covid-19 vaccinations.